Accessing Totally Implantable Venous Access Systems on the day of Placement does not Significantly Increase the Risk of Infection. Issue 3 (May 2016) - Young, Shamar J.; Young, Linda J.; Vogel, Jeffery; Sutkowski, Raymond; Venkataperumal, Satish
Purpose: Totally implantable venous access systems (ports) are commonly placed and have a low complication rate. The most common complication is infection, which can have very negative effects on patients resulting in hospitalization and/or treatment delay in the setting of neoplasm. While a number of variables have been studied in relation to diminishing infectious rates, one remaining question is the effect of accessing the port on day of placement, which is the aim of this retrospective study. Materials and methods: After internal review board approval the electronic medical records of 2, 006 patients who underwent port placement between 10/1/2008 and 9/30/2013 were reviewed. Of these patients 628 were excluded as they did not have complete placement and removal data available, leaving 1378 patients in our cohort. Results: There was a significantly longer number of infection-free catheter days in the out-patient cohort as compared to the in-patient cohort (p = 0.027). In-patients mean day after placement when the port was first accessed (DAP) (0.5) was statistically earlier (closer to placement) than the out-patients DAP (7.2) (p<0.0001). However, the increased likelihood of infection could not be explained by DAP (p = 0.2029) even when controlling for in-patient and out-patient status (p = 0.97). Conclusions: Accessing the port on the day of placement does not significantly contribute to an increased likelihood of infection. This study seems to indicate that placing a port on the first day of outpatient therapy likely optimally balances respect for patient time with infection control.